The prediction of mercury bioavailability for common carp (Cyprinus carpio L.) using the DGT technique in the presence of chloride ions and humic acid - Pelcová, Pavlína; Vičarová, Petra; Dočekalová, Hana; Poštulková, Eva; Kopp, Radovan; Mareš, Jan; Smolíková, Vendula (Chemosphere, 2018)
The ability of the DGT technique to predict Hg2+ bioavailability for input tissues (skin, gills, and scales) of common carp in the presence of chloride ions and humic acid (HA) was evaluated. The mercury accumulation by the DGT units and input tissues of carp decreased with an increasing concentration of chloride ions (29-180 mg L-1) and HA (0-5 mg L-1). In the presence of chloride ions and HA, statistically significant correlations (Pearson's correlation coefficients 0.731-0.954) were determined between the rate of mercury accumulation by input tissues of carp and the rate of mercury accumulation by the DGT units. The laboratory experiments suggest the possibility of using the DGT technique for predicting the mercury bioaccumulation in natural aquatic ecosystems instead of commonly used input tissues of fish.
Keywords: Humic Substances; Ecosystem; zvířata; chloridy; ekosystém; kůže; Biological Availability; Skin; Animal Scales; Mercury; Water Pollutants, Chemical; Animals; metody; kapři; Methods; žábry; rtuť; Gills; biologická dostupnost; chemické látky znečišťující vodu; zvířecí šupiny; Carps; Chlorides; huminové látky